Training For Social Media Management of Gerabah (Handycrafts) Marketing in Banyumulek Village, West Lombok Regency - Yohanes, Yulanda Trisula Sidarta; Muhlis; Hartin Nur Khusnia (Prospect: Jurnal Pemberdayaan Masyarakat, 2023)
Community service with the topic of training on social media management of pottery product marketing Banyumulek Village aims to make potters become able to edit content design using the Canva application, become able to design product marketing messages to be published on each social media account, as well as become able to manage posts on social media potters in Banyumulek Village, West Lombok Regency. The scope of this activity is digital content creation training through the Canva. The method is carried out through 3 (three) stages, namely: lectures, clarification of social media, and practice to manage social media in marketing. The fact in the field is that participants have not been optimal in managing social media for the promotion of earthenware products. The result of the activity obtained was that participants gained additional insights after being taught to use the Canva to help design content in the promotion of pottery products. From the activity, participants were divided into 3 (three) small groups to be trained using the Canva by the service team. This activity has benefits for participants because by using the Canva, the content design becomes more attractive because there is already a template that can be accessed by participants.